The INCREASING THE MINIMUM COMPETENCY ASSESSMENT THROUGH THE KAMPUS MENGAJAR PROGRAM AT SDN TARUMSARI, BANDUNG REGENCY - Nurfaidah, Siti Sholiha; Azis Lukman Praja; Nurul Fazriyah (Pasundan International of Community Services Journal (PICS-J), 2023)
It is very important for students to master literacy and numeracy skills so that they can live a good career and social life. Because through good literacy and numeracy skills, individuals can make the right decisions. However, it is unfortunate that some data shows that the literacy and numeracy results of students in Indonesia are not encouraging enough. This then encourages various efforts to resolve these problems. The Teaching Campus under the auspices of the MBKM Program is one of the leading programs to continue to improve Indonesia's numeracy literacy capabilities. On this occasion, the school assigned to Teaching Campus 5 in question was SDN Tarumsari. The method we use to increase students' numeracy literacy scores is school observation, pretest, FKKS, program design, program implementation, and posttest. The findings from the results of the program implementation were that there was an increase in students' numeracy literacy scores in the pretest and posttest. Therefore, we believe that the program designed has been implemented well in line with expectations.